Psychometric reliability of the NeuroVR-based virtual version of the Multiple Errands Test - Cipresso, Pietro; Serino, Silvia; Pedroli, Elisa; Riva, Giuseppe; Albani, Giovanni (2013 7th International Conference on Pervasive Computing Technologies for Healthcare and Workshops, 2013)
This study aim at testing the psychometric reliability of the NeuroVR-based virtual version of the Multiple Errands Test (VMET). In a first experiment two independent researchers scored 11 videos, each one of a subject running the VMET. In a second experiment 7 researcher scored two videos, each one of a subject running the VMET. Results showed the extent to which a disagreement become critical in VMET.